2020
DOI: 10.1007/s11684-020-0803-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and the traditional Chinese medicine therapeutic characteristics of 293 COVID-19 inpatient cases

Abstract: Coronavirus disease 2019 (COVID-19) is now pandemic worldwide and has heavily overloaded hospitals in Wuhan City, China during the time between late January and February. We reported the clinical features and therapeutic characteristics of moderate COVID-19 cases in Wuhan that were treated via the integration of traditional Chinese medicine (TCM) and Western medicine. We collected electronic medical record (EMR) data, which included the full clinical profiles of patients, from a designated TCM hospital in Wuha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 32 publications
(28 reference statements)
1
39
0
Order By: Relevance
“…In a Chinese meta-analysis including 6686 patients, the reported PPE of the anorexia symptom was the same as that in this study, 21% [ 133 ]. Usage of experimental drugs and herbal medicine against COVID–19 infections might be a possible explanation for the higher rate of anorexia symptom PPE values [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a Chinese meta-analysis including 6686 patients, the reported PPE of the anorexia symptom was the same as that in this study, 21% [ 133 ]. Usage of experimental drugs and herbal medicine against COVID–19 infections might be a possible explanation for the higher rate of anorexia symptom PPE values [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dioscorea polystachya Turcz., tuber are included to relieve gastrointestinal symptoms in COVID-19 patients, such as abdominal distention, loss of appetite, and diarrhea. Glycyrrhiza glabra L., root and rhizome, raw or honeyed and Dioscorea polystachya Turcz., tuber belong to "Bu-Yi" herbs in TCM and are used to treat patients with fatigueone of the main symptoms in COVID-19 patients (Li et al, 2020b), known to worsen throughout COVID-19 disease progression and to hinder patient recovery. In summary, in addition to reducing lung damage, LCDD may reduce other tissue damage, such as in the kidney, liver, heart and brain.…”
Section: For Treatment Of All Stages-lung Cleansing and Detoxifying Dmentioning
confidence: 99%
“…The application of the traditional Chinese medicine for the treatment of SARS-CoV-2 is currently based on the treatments used for SARS-CoV, thanks to their similarities (Gong et al, 2008;Nguyen et al, 2012). A retrospective observational study carried out in 293 patients affected by COVID-19 showed that the prescription of common herbs used in folk medicine may be considered as an integrative approach for COVID-19 management, since some popularly used drugs, such as moxifloxacin, oseltamivir, and Arbidol, are not always effective in reducing severe symptoms (Shu et al, 2020). However, since COVID-19 is a complex clinical disease that is often complicated by severe disorders, as clotting activation, rapid degeneration of parenchyma, and organ failure, additional studies will be requested to confirm the efficacy of traditional medicine approach alone or in combination with other drugs.…”
Section: Therapeutic Approaches For the Treatment Of Severe Acute Resmentioning
confidence: 99%
“…Among the other antiviral strategies, umifenovir (Arbidol) is a new antiviral option approved in China for the management of COVID-19: it prevents virus entry by binding to hemagglutinin ( Aktas et al, 2020 ). However, clinical studies on umifenovir showed that the administration of umifenovir alone was ineffective, whereas the combination with other antivirals might ameliorate viral clearance and improve lung damage ( Chen et al, 2020 ; Song et al, 2020 ).…”
Section: Therapeutic Approaches For the Treatment Of Severe Acute Resmentioning
confidence: 99%